One step endoscopic ultrasound guided management of pelvic abscesses: a case series - Zator, Zachary (Therap Adv Gastroenterol, 2018)
BACKGROUND: Endoscopic management of pelvic abscesses not amenable to percutaneous drainage has been described. The technique employs endoscopic ultrasound (EUS)-guided placement of stents or drains, which may require multiple procedures, is cumbersome and uncomfortable for the patient. We describe the successful management of these abscesses in a single step involving EUS-guided lavage and instillation of antibiotics. METHODS: Six consecutive patients with seven symptomatic pelvic abscesses not amenable to percutaneous drainage were referred for EUS-guided drainage. The abscesses were aspirated with a 19-gauge needle under EUS guidance and serially lavaged with an equal aspirate to instillation volume of sterile saline until cleared of pus. The residual cavity was then instilled with gentamicin 40 mg/ml. Patients were followed clinically and radiographically with repeat computed tomography or magnetic resonance imaging. RESULTS: All patients had rapid resolution of symptoms. The abscesses disappeared completely in four patients. One patient with recurrent diverticulitis and abscess had marked decrease in abscess size and inflammation to permit planned sigmoid resection. One patient with Crohn’s disease had clinical improvement and marked decrease in abscess size, permitting outpatient management of Crohn’s disease. CONCLUSIONS: EUS-guided lavage and instillation of antibiotics is a simple, one-step approach in the management of pelvic abscesses and may obviate the need for prolonged drain management and repeat procedures in select cases.